ヒガシナンキョク ソウヤカイガン ラングホブデイキ ニアル ヒョウガ イケ (カショウ) ノ タネンセイ セツテイボウ ケッカイ ケッカイ ニ トモナッタ カクラン ニヨル コショウ ナイ ト ソノ シュウヘン ショクセイ ヘノ エイキョウ ニ カンスル コウサツ - 工藤, 栄; クドウ, サカエ; 田邊, 優貴子; タナベ, ユキコ; 井上, 武史; イノウエ, タケシ; 伊村, 智; イムラ, サトシ; 神田, 啓史; カンダ, ヒロシ; Kudoh, Sakae; Tanabe, Yukiko; et al. (2009)
P(論文) 南極の陸域環境の植物の分布と定着は,洪水をも含む環境の物理的撹乱による制限を強く受けていると考えられる.近年(第47次観測隊以降),日本南極地域観測隊の活動を通じ,東南極宗谷海岸のラングホブデ域にある氷河池(仮称)の多年性雪の堤防に大きな穴が開き決壊したことを確認した.同様の現象は約25年前にも報告されている.以前の穴はその後閉塞し,今回の決壊直前まで氷河融解水が涵養した湖沼となっていたが,現在ではその湖水のほとんどが失われ,湖の面積は著しく縮小している.ラングホブデ南部にある隣接したいくつかの渓谷及び湖沼は,土壌藻類・地衣類・蘚類や湖底藻類蘚類群落が発達した地域として知られている.これらの中で,氷河池内やこの雪の堤防の下流側の渓谷(やつで沢)にはごく乏しい植生しか見出すことはできない.この対照的に貧弱な植生の分布と定着状態は,繰り返し発生する堤防の決壊による物理的撹乱が湖沼内及びその下流側での植物の分布・定着を制限した結果であると考えられる.この報告を通じ,著者らはこの地域の氷床の融解量の変化の評価とともに,露岩域での生態学的研究及びこのエリアで今後とも行われる観測活動に際しての安全確保という観点から,この多年性雪堤防と氷河池の長期監視の重要性を訴えるものである. The distribution and colonization of flora in Antarctica may be limited by disturbance events, including flooding. Recently, we observed a large hole in the perennial snow dam below Lake Hyoga Ike (temporary name), located in the Langhovde region on the Sôya Coast in East Antarctica. This phenomenon was also reported by a previous Japanese Antarctic Research Expedition, almost 25 years earlier. The earlier breakage was subsequently closed and the lake was refilled. At present, the surface area of the lake has decreased significantly due to the loss of water. Many of the neighboring valleys and lakes in the southern part of the Langhovde area contain well-developed colonies of algae, mosses, and lichens. By contrast, both Lake Hyoga Ike and the river below the snow dam contain very little flora. Such a contrast in the distribution and colonization of flora suggests that the repeated occurrence of physical disturbances, induced by breaching of the dam, may be a critical factor limiting flora in this ice-free region of Antarctica. We recommend long term observation of the fate of the ice cave and changes in the lake level for the purpose of evaluating climatic change and ecology. The observations also contribute to the maintenance of safety in the field works in this area. departmental bulletin paper